Risk Management of Neurobehavioral Health of Tyre Manufacturing Industry Eorkers Exposed to Naphtha - Ismail, Norazura . (2011)
Introduction: Neurobehavioral effects on cognitive functioning and motor disturbances were linked to organic solvents even in setting exposure standards in the workplace which may interfere with job tasks resulting in costly injuries and lost of productivity. This study is aimed to assess and manage the risks of naphtha exposure and the neurobehavioral health effects among workers in a tyre manufacturing industry. Methodology: A cross-sectional study was carried out in Phase I, followed by an intervention study in Phase II. A total of 119 male workers exposed to naphtha were universally recruited as the exposed group, while 72 male administrative workers who did not exposed to naphtha were selected as the unexposed group. In Phase I, questionnaires were used to collect the information on general background, occupational profile and the risk factors. Environmental and personal air monitoring were carried out using a portable volatile organic compound (VOC) monitor and personal air sampling pump. Neurobehavioral performance was measured using the Neurobehavioral Core Test Battery (NCTB). The respondents from the Phase 1 were then followed up in the second phase for the intervention study. They were later undergone a workplace health promotion (WHP) programme for three consecutive days in order to improve their knowledge, attitude and practice (KAP) of safe handling of naphtha. Seminar and small group discussion were carried out in this WHP programme. The pre- and post- questionnaires were administered before and after the WHP programme among the respondents. Results: The range of VOC concentration was from 1.10 to 546.10 ppm, with the highest mean of 92.93 (SD153.63) ppm found in the “repair” area. Laboratory analysis found various organic compounds such as 2-methyl pentane, hexane, methyl cyclopentane, heptane, cyclohexane and toluene made up the liquid naphtha. The mean neurobehavioral score of the exposed group was significantly lower than the unexposed group (p=0.001). There were significant differences in the tests of Digit Symbol (p=0.001), Pursuit Aiming (p<0.001), and Santa Ana Manual Dexterity for dominant hand (p=0.021) and non-dominant hand (p=0.048) scores between the 2 groups. However, there was no correlation between personal air naphtha concentration and the total NCTB scores among the exposed group. The personal air naphtha concentrations among the exposed group were significantly higher than the unexposed group (p<0.001). Factors such as duration of work, total years of education, age, household income, knowledge and practice influenced the neurobehavioral performance. The level of knowledge among workers was significantly higher after the intervention programme (p<0.05). Conclusion: An early sign of neurobehavioral impairment was identified among the exposed group to low level of VOC and naphtha exposure. Therefore, attention to the chronic adverse health effects of organic solvent exposure should be given for safe and healthy working environment. The WHP package is a good mechanism of communicating risk at the workplace for an early detection and prevention of adverse health effect. A continual education should be implemented through various methods to enhance and retain workers’ good performance at the workplace. Key words: Risk management, naphtha, neurobehavioral health, knowledge, attitude, practice, occupational health promotion.